Poliphony in Andrea Camilleri’s II birraio di Preston - Prunster, Nicole (Spunti e Ricerche, 2016)
II birraio di Preston (1995) is a recent addition to a series of famous Italian novels that explore reactions to the Risorgimento in Sicily. Set in the fictitious town of Vigata in the still-unsettled atmosphere of 1874, it is the third of four historical parodies by Camilleri. The novel was published the year after La forma dell’acqua, the first of the Montalbano gialli, and a year before Il cane di terracotta, the second in the series. Readers of these gialli are already familiar with Camilleri’s use of language, most notably, Sicilian dialect. In II birraio di Preston, he employs a far greater linguistic variety in satirising official representatives from the north of Italy who would seek to impose their language and culture on the southern barbarians. The resulting humour is an effective critical weapon directed at the hegemonic elite that views Unification as a moral right.